The Impact Of Online Marketing And Product Quality On Consumer Purchase Intention Of Ms Glow Skincare In Bengkulu City - Zuzan, Analia; Monique, Eska Prima; Indriasari, Nia (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
his research method uses quantitative research and data collection using questionnaire techniques, with a sample of 120 respondents. The results showed that multiple linear regression Y = 10,002 + 0.004 X1 + 0.997 X2+ 0.120. Where the coefficient is positive, it means that there is a positive or unidirectional relationship between the variables of online marketing and product quality on consumer interest in skincare MS Glow Bengkulu City. The results show that the online marketing test results (XI) show tcount 2.005> ttable 1.980 and significant 0.047 <0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that online marketing has a positive and significant effect on consumer buying interest in skincare MS Glow Bengkulu City. The results of the product quality test (X2) show tcount 31.466> ttable 1.980 and sigfinikasi 0.00<0.05, then the results of the hypothesis Ha is accepted and Ho is rejected, meaning that product quality has a positive and significant effect on consumer buying interest in skincare MS Glow Bengkulu City. The results of comparing the Fcount value with Ftable, the Fcount value is greater than the Ftable value, namely 48.903> 3.07, it is concluded that Accepting the Hypothesis, meaning that there is a simultaneous influence between online marketing (XI), product quality (X2) on buying interest (Y) MS Glow skincare consumers Bengkulu City. This can be seen at a significance level of 0.000 <0.05